Red cell hypoplasia, thrombocytosis, and leucocytosis: myelodysplastic and proliferative syndrome. Issue 11 (November 1988) - Craig, A; Geary, C G; Love, E M; Liu-Yin, J
Abstract : Three patients with chronic red cell aplasia also showed thrombocytosis or granulocytosis, or both. All had morphological evidence of myelodysplasia on examination of bone marrow aspirate but none had a detectable chromosomal abnormality. These patients seem to provide evidence of a separate entity within the spectrum of myelodysplastic and myeloproliferative disease.